Artritis reumatoide y riesgo cardiovascular - Karsulovic C., Claudio; Guerrero P. , Julia; Goecke S., Annelise (Revista Hospital Clínico Universidad de Chile, 2019)
Cardiovascular disease (CVD) is the most frequent cause of premature death according to datafrom the American Heart Association and World Health Organization. Incidence and prevalence areon the rise. Rheumatoid Arthritis (RA) is the most common autoimmune disease. It is a chronic andsystemic disease characterized by articular involvement with deformity ranging from persistentpain to premature disability. CVD is the most frequent cause of death in RA patients, even morethan in diabetes mellitus 2 or chronic kidney disease. Multiple CVD risk scales have been tested inorder to obtain a more accurate prediction of premature death by stroke or myocardial infarctionin RA patients. Most of the scales, even those adjusted including RA features like inflammationand antibodies titles, have failed to properly predict the real CVD risk. Individually, RA specificautoantibodies have been related with increased CVD risk and multiple mechanistic explanationshave arisen, generating even a new concept called “Autoimmune Atheromatosis”. Nevertheless,this association fails to give a full understanding of the accelerated and aggressive atheromatosisprocess that RA patients develop. New studies oriented to mechanistic explanations arenecessary in order to develop new diagnostic targets and prevention strategies.